Optimal duration of prone positioning in patients with acute respiratory distress syndrome: a protocol for a systematic review and meta-regression analysis. Issue 9 (10th September 2018) - Kamo, Tetsuro; Aoki, Yoshitaka; Fukuda, Tatsuma; Kurahashi, Kiyoyasu; Yasuda, Hideto; Sanui, Masamitsu; Nango, Eishu; Abe, Takayuki; Lefor, Alan Kawarai; Hashimoto, Satoru
Abstract : Introduction: Several systematic reviews and meta-analyses have demonstrated that prolonged (≥16 hours) prone positioning can reduce the mortality associated with acute respiratory distress syndrome (ARDS). However, the effectiveness and optimal duration of prone positioning was not fully evaluated. To fill these gaps, we will first investigate the effectiveness of prone positioning compared with the conventional management of patients with ARDS, regarding outcomes using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system. Second, if statistical heterogeneity in effectiveness with regard to short-term mortality (intensive care unit death or ≤30-day mortality) is shown, we will conduct a meta-regression analysis to explore the association between duration and effectiveness, and determine the optimal duration of prone positioning. Method and analysis: Relevant studies are collected using PubMed/MEDLINE, Embase, Cochrane Central Register of Controlled Trials and the WHO International Clinical Trials Platform Search Portal. Randomised controlled trials comparing prone and supine positioning in adults with ARDS will be included in the meta-analysis. Two independent investigators will screen trials obtained by search eligibility and extract data from selected studies to standardised data recording forms. For each selected trial, the risk of bias and quality of evidence will be evaluated using the GRADE system. Meta-regression analyses will be performed to identify the most important factors associated with short-term mortality, and subgroup analysis will be used to analyse the following: duration of mechanical ventilation in the prone position per day, patient severity, tidal volume and cause of ARDS. If heterogeneity or inconsistency among the studies is detected, subgroup analysis will be conducted on factors that may cause heterogeneity. Ethics and dissemination: This study requires no ethical approval. The results obtained from this systematic review and meta-analysis will be disseminated through international conference presentations and publication in a peer-reviewed journal. PROSPERO registration number: CRD42017078340.